DIGITAL TRANSFORMATION IN FARMER-TO-CONSUMER VEGETABLE MARKETING: OPPORTUNITIES AND BARRIERS - Dr. Sandeep N Jagdale; Mr. Abhale Ganesh Arun (The Bioscan, 2026)
The agricultural sector has been undergoing substantial changes due to advances in digital technologies, and these shifts are increasingly influencing how vegetables are marketed directly from farmers to consumers. Digital transformation includes the use of technology such as the Internet of Things (IoT), blockchain, artificial intelligence (AI), mobile applications, and e-marketplaces. These technologies present significant prospects to improve the efficiency, transparency, and sustainability of vegetable supply chains.